Mapping the relationships between structural brain MRI characteristics and sleep electroencephalography patterns: the Multi-Ethnic Study of atherosclerosis - Kozhemiako, Nataliia; Heckbert, Susan R; Castro-Diehl, Cecilia; Paquet, Caitlin B; Bertisch, Suzanne M; Habes, Mohamad; Fohner, Alison E; Bryan, Robert Nick; Nasrallah, Ilya; Hughes, Timothy M; Redline, Susan; Purcell, Shaun M (Sleep (New York, N.Y.), 2025)
While brain morphology is well-established as a key factor influencing overall brain function, little is known about how brain structural properties are associated with oscillatory activity, particularly during sleep. In this study, we analyzed whole-night sleep electroencephalography (EEG) and brain structural MRI data from a subset of 621 individuals in the Multi-Ethnic Study of Atherosclerosis to explore the relationship between brain structure and sleep EEG properties. We found that larger total white matter (WM) volume was associated with higher absolute broad-band power, regardless of sleep stage, likely reflecting WM contribution to enhanced synchronization across cortical regions and reduced activation attenuation via long-range myelinated fibers. Additionally, both WM fractional anisotropy and thalamic volume showed a negative association with relative slow power and a positive association with delta power during non-rapid eye movement sleep. This was mirrored in the duration of slow oscillations, both overall and when divided into slow-switching and fast-switching types, with their ratio additionally linked to total WM volume. Furthermore, we observed strong but largely independent effects of age and sex on sleep EEG and structural magnetic resonance imaging (MRI) metrics, suggesting that sleep EEG captures aging processes and sex-specific features that extend beyond the macro-scale brain morphology changes examined here. Overall, these findings deepen our understanding of how structural brain properties influence sleep-related oscillatory activity.